Antimicrobial potential of green synthesized CeO2 nanoparticles from Olea europaea leaf extract - Maqbool Q (Dove Medical Press, 2016)
Qaisar Maqbool,1 Mudassar Nazar,1 Sania Naz,2 Talib Hussain,3 Nyla Jabeen,4 Rizwan Kausar,5 Sadaf Anwaar,4 Fazal Abbas,6,7 Tariq Jan6 1Department of Biotechnology, Virtual University of Pakistan, Lahore, Pakistan; 2Department of Biotechnology, Quaid-i-Azam University, Islamabad, Pakistan; 3National Institute of Vacuum Science and Technology (NINVAST), Islamabad, Pakistan; 4Department of Biotechnology and Bioinformatics Lab., International Islamic University, Islamabad, Pakistan; 5Department of Chemistry, University of Sargodha, Sargodha, Pakistan; 6Department of Physics, International Islamic University, Islamabad, Pakistan; 7Interdisciplinary Research Organization, University of Chakwal (UOC), Chakwal, Pakistan Abstract: This article reports the green fabrication of cerium oxide nanoparticles (CeO2 NPs) using Olea europaea leaf extract and their applications as effective antimicrobial agents. O. europaea leaf extract functions as a chelating agent for reduction of cerium nitrate. The resulting CeO2 NPs exhibit pure single-face cubic structure, which is examined by X-ray diffraction, with a uniform spherical shape and a mean size 24 nm observed through scanning electron microscopy and transmission electron microscopy. Ultraviolet-visible spectroscopy confirms the characteristic absorption peak of CeO2 NPs at 315 nm. Fourier transform infrared spectroscopy reflects stretching frequencies at 459 cm-1, showing utilization of natural components for the production of NPs. Thermal gravimetric analysis predicts the successful capping of CeO2 NPs by bioactive molecules present in the plant extract. The antimicrobial studies show significant zone of inhibition against bacterial and fungal strains. The higher activities shown by the green synthesized NPs than the plant extract lead to the conclusion that they can be effectively used in biomedical application. Furthermore, reduction of cerium salt by plant extract will reduce environmental impact over chemical synthesis. Keywords: XRD, SEM, TEM, FTIR, antibacterial, antifungal, nanomedicine, green fabrication